Inflammatory Diseases, Inflammatory Biomarkers, and Alzheimer Disease: An Observational Analysis and Mendelian Randomization - Huang Jian; Su Bowen; Karhunen Ville; Gill Dipender; Zuber Verena; Ahola-Olli Ari; Palaniswamy Saranya; Auvinen Juha; Herzig Karl-Heinz; Keinänen-Kiukaanniemi Sirkka; Salmi Marko; Jalkanen Sirpa; et al. (American Academy of Neurology, 2025)
Objectives: Whether chronic autoimmune inflammatory diseases causally affect the risk of AD is controversial. We characterised the relationship between inflammatory diseases and the risk of AD and explore the role of circulating inflammatory biomarkers in the relationships between inflammatory diseases and AD.
Methods: We performed observational analyses for chronic autoimmune inflammatory diseases and risk of AD using data from 2,047,513 participants identified in the UK Clinical Practice Research Datalink (CPRD). Using data of a total of more than 1,100,000 individuals from 15 large scale genome-wide association study (GWAS) datasets, we performed two-sample Mendelian randomisation (MR) to investigate the relationships between chronic autoimmune inflammatory diseases, circulating inflammatory biomarker levels, and risk of AD.
Results: Cox regression models using CPRD data showed that overall incidence of AD was higher among patients with inflammatory bowel disease (IBD) (hazard ratio (HR)=1.17; 95%CI 1.15 to 1.19; P-value=2.1×10-4), other inflammatory polyarthropathies & systematic connective tissue disorders (OID) (HR=1.13; 95%CI 1.12 to 1.14; P-value=8.6×10-5), psoriasis (HR=1.13; 95%CI 1.10 to 1.16; P-value=2.6×10-4), rheumatoid arthritis (RA) (HR=1.08; 95%CI 1.06 to 1.11; P-value=4.0×10-4), and multiple sclerosis (MS) (HR=1.06; 95%CI 1.04 to 1.07; P-value=2.8×10-4) compared to the age (± 5 years) and sex-matched comparison groups free from all inflammatory diseases under investigation. Bidirectional MR analysis identified relationships between chronic autoimmune inflammatory diseases and circulating inflammatory biomarkers. Particularly, circulating monokine induced by gamma interferon (MIG) level was suggestively associated with a higher risk of AD (odds ratio from inverse variance weighted (ORIVW)=1.23; 95%CI 1.06 to 1.42; PIVW=0.007), and lower risk of Crohn's disease (ORIVW=0.73; 95%CI -0.62, 0.86; PIVW=1.3×10-4). Colocalisation supported a common causal SNP for MIG and Crohn's disease (posterior probability=0.74) but not AD (posterior probability=0.03). Using a two-sample MR approach, genetically predicted risks of inflammatory diseases were not associated with higher AD risk.
Conclusion: Our data suggest that the association between inflammatory diseases and risk of AD is unlikely to be causal and may be a result of confounding. In support, while inflammatory biomarkers showed evidence for causal associations with inflammatory diseases, evidence was weak that they affected both inflammatory disease and AD.